Abrasion-resistant environment-friendly spunlace nonwoven fabric and preparation method thereof

CN120174545BActive Publication Date: 2026-10-16ZHEJIANG WANGJIN NONWOVENS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510320586.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2026-10-16
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

[0004]鉴于现有技术中,一般无纺布无法兼顾环保性和耐磨性的问题,本发明提供一种耐磨环保水刺无纺布及其制备方法

Benefits of technology

[0028]This invention first involves melting maleic anhydride to graft carboxyl-terminated polylactic acid (PLA), then reacting it with chitosan, polyether polyamine, and trimesoyl chloride to obtain modified PLA. Next, the modified PLA is composite-spun with high-shrinkage polyester to obtain a bicomponent fiber with a parallel structure. Finally, a wear-resistant and environmentally friendly spunlace nonwoven fabric is produced through web laying and hydroentangling processes. In this invention, after modification, the PLA's main chain structure remains essentially unchanged, while a cross-linked network structure is formed in its branched structure. This essentially maintains the good biocompatibility, degradability, and skin-friendliness of PLA while improving its mechanical strength and wear resistance. Furthermore, the composite spinning of the modified PLA with high-shrinkage polyester to obtain a bicomponent fiber with a parallel structure results in a spiral curl due to the significant difference in thermal shrinkage properties between the two components during the spinning process. This makes the resulting bicomponent fiber fluffy, further endowing it with softness and skin-friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005317308440000071
    Figure BDA0005317308440000071
  • Figure BDA0005317308440000081
    Figure BDA0005317308440000081
Patent Text Reader

Abstract

The present application relates to a kind of wear-resistant environment-friendly spunlace nonwoven fabric, it is by high shrinkage polyester / modified polylactic acid parallel structure's double-component fiber composition, the modified polylactic acid is carboxyl-terminated polylactic acid after molten grafting with maleic anhydride, then with chitosan, polyether polyamine, trimesoyl chloride reaction is obtained;The amount of maleic anhydride is 5~8wt% of carboxyl-terminated polylactic acid;The mass ratio of maleic anhydride, chitosan, polyether polyamine, trimesoyl chloride is 1:(1.2~1.5):(0.4~0.6):(0.05~0.08).The spunlace nonwoven fabric of the present application has excellent wear resistance and good biodegradability, and skin-friendly soft, that is, wear resistance and environmental protection are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nonwoven fabric technology, specifically relating to a wear-resistant and environmentally friendly spunlace nonwoven fabric and its preparation method. Background Technology

[0002] Nonwoven fabrics, also known as non-woven textiles, are composed of oriented or randomly arranged fibers. Due to their good breathability and softness, they are widely used in medical and health products, industrial and agricultural products, and other fields. However, most nonwoven fabrics are difficult to biodegrade, causing environmental pollution. For example, polypropylene fiber-based nonwoven fabrics have excellent chemical resistance and abrasion resistance, but they are difficult to degrade and have poor skin-friendly softness. Therefore, the application of biodegradable materials in nonwoven fabrics has become a focus of attention. However, the mechanical properties of conventional biodegradable materials in existing technologies are very limited. For example, polylactic acid fiber is made from renewable resources such as corn, wheat, and potatoes. It is environmentally friendly, easily degradable, and has good skin-friendliness, making it a good biodegradable material. However, its poor mechanical strength limits its application in abrasion-resistant nonwoven fabrics.

[0003] Patents CN102336961B and CN 102336929B disclose a PP spunbond nonwoven fabric composite material modified with heavy calcium carbonate and corn starch, and a PP spunbond nonwoven fabric modified with corn starch, respectively. Both are environmentally friendly and biodegradable. However, the addition of corn starch reduces the tensile strength and abrasion resistance of the nonwoven fabric. Therefore, it is necessary to develop a nonwoven fabric that can balance environmental friendliness and abrasion resistance. Summary of the Invention

[0004] Given that existing technologies generally fail to balance environmental friendliness and abrasion resistance in nonwoven fabrics, this invention provides an abrasion-resistant and environmentally friendly spunlace nonwoven fabric and its preparation method. This invention uses high-shrinkage polyester (HSPET) and modified polylactic acid in a parallel structure to produce composite fibers through bicomponent spinning. These fibers are then carded into a web and subjected to a spunlace process to obtain a skin-friendly, environmentally friendly, and abrasion-resistant nonwoven fabric.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] A wear-resistant and environmentally friendly spunlace nonwoven fabric is composed of a bicomponent fiber with a high-shrinkage polyester / modified polylactic acid parallel structure. The modified polylactic acid is obtained by melt grafting maleic anhydride onto carboxyl-terminated polylactic acid, followed by reaction with chitosan, polyether polyamine, and trimesoyl chloride. The amount of maleic anhydride used is 5-8 wt% of the carboxyl-terminated polylactic acid. The mass ratio of maleic anhydride, chitosan, polyether polyamine, and trimesoyl chloride is 1:(1.2-1.5):(0.4-0.6):(0.05-0.08).

[0007] Further, the mass ratio of maleic anhydride, chitosan, polyether polyamine, and trimesoyl chloride is 1:(1.3-1.4):(0.4-0.5):(0.06-0.07).

[0008] Furthermore, the modified polylactic acid is prepared by a method comprising the following steps:

[0009] (L1) Carboxyl-terminated polylactic acid, maleic anhydride and initiator are mixed and then melt-grafted to obtain grafted polylactic acid;

[0010] (L2) Grafted polylactic acid, chitosan, polyether polyamine and catalyst are dissolved in a solvent and reacted at 5-10℃ for 2-4 hours under an inert atmosphere. The temperature is then raised to 60-80℃ and the reaction continues for another 2-4 hours. Then, pyromellitic chloroformyl chloride and acid-binding agent are added and reacted at 10-25℃ for 0.5-1 hours. After the reaction is completed, the mixture is rotary evaporated and dried to obtain modified polylactic acid.

[0011] Preferably, in step (L1), the initiator is selected from at least one of dicumyl peroxide and ditert-butyl peroxide, and the amount of initiator is 0.1 to 0.2 wt% of the carboxyl-terminated polylactic acid; the melt grafting conditions are: carried out in a twin-screw extruder, with a reaction temperature of 180 to 200°C and a time of 0.5 to 1.5 h.

[0012] Preferably, in step (L2), the catalyst is at least one of FeCl3 and AlCl3, and the amount of catalyst used is 0.5-0.8 wt% of chitosan; the solvent is a mixture of a polar aprotic organic solvent and an organic acid, wherein the volume percentage of the organic acid is 1-3%, the polar aprotic organic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone, and the organic acid is at least one of acetic acid, oxalic acid, and citric acid. The addition of organic acid can improve the solubility of chitosan.

[0013] Preferably, in step (L2), the inert atmosphere is nitrogen and / or argon.

[0014] Preferably, in step (L2), the acid-binding agent is selected from at least one of triethylamine and pyridine, and the mass of the acid-binding agent is 1.5 to 2.0 times that of pyromellitic acid chloride.

[0015] Furthermore, in the bicomponent fiber with the parallel structure, the modified polylactic acid accounts for 40-50% by mass, and the remainder is high-shrinkage polyester.

[0016] Further, the fineness of the parallel-structured bicomponent fiber is 1.5–3.0 dtex, and the length is 30–50 mm. The parallel-structured bicomponent fiber is prepared by a method including the following steps: modified polylactic acid is added to an extruder and heated to melt, then enters the spinning die through a melt filter, melt conveying pipe, and metering pump, and is evenly distributed to the first spinning assembly through the spinning die; high-shrinkage polyester is added to another extruder and heated to melt, then enters the spinning die through a melt filter, melt conveying pipe, and metering pump, and is evenly distributed to the second spinning assembly through the spinning die; composite spinning is performed at the outlet, followed by cooling, stretching, winding, and cutting to produce the parallel-structured bicomponent fiber.

[0017] Preferably, the high-shrinkage polyester and modified polylactic acid are dried at 65-80°C for 8-12 hours before being added to the extruder, and the composite spinning temperature is 230-250°C.

[0018] Furthermore, the intrinsic viscosity of the high-shrinkage polyester is 0.65–0.72 dl / g, and the melting point is 200–220°C. High-shrinkage polyester is a differentiated polyester with a high shrinkage rate, generally obtained by introducing a third monomer during polyester synthesis. The introduction of the third monomer disrupts the regularity of the molecular chain and increases the shrinkage rate. For example, high-shrinkage polyester can be obtained by using dimethyl terephthalate (DMT) and ethylene glycol (EG) as raw materials and adding the third monomer dimethyl isophthalate (DMI). The high-shrinkage polyester described in this invention is commercially available.

[0019] Furthermore, the intrinsic viscosity of the terminal carboxyl polylactic acid is 1.30–1.50 dl / g, and the melting point is 160–190 °C.

[0020] Furthermore, the intrinsic viscosity of the chitosan is 2.0–2.5 dl / g, and the degree of deacetylation is 80–90%. The degree of deacetylation affects both the reactivity and mechanical properties of chitosan. A high degree of deacetylation results in high strength and high reactivity, but excessively high deacetylation leads to brittleness and poor solubility, which is detrimental to the performance of the final bicomponent fiber and causes inconvenience in the preparation process.

[0021] Furthermore, the polyether polyamine is at least one of polyether diamine and polyether triamine, and the number average molecular weight of the polyether polyamine is 400 to 1000.

[0022] Secondly, the present invention also provides a method for preparing the above-mentioned wear-resistant and environmentally friendly spunlace nonwoven fabric, comprising the following steps: opening and combing high-shrinkage polyester / modified polylactic acid parallel structure bicomponent fibers into a web to form a fiber web layer; then reinforcing it with hydroentangling, drying it, and rolling it into a roll to obtain the wear-resistant and environmentally friendly spunlace nonwoven fabric.

[0023] Preferably, the combing and forming of the web is done in parallel or cross-laid form; the hydroentangling reinforcement process is as follows: hydroentangling pressure 4-10 MPa, number of hydroentangling passes 3-6.

[0024] Preferably, the wear-resistant nonwoven fabric can also undergo surface perforation and protrusion processes, the perforation and protrusion processes being well known to those skilled in the art.

[0025] Polylactic acid (PLA) possesses excellent biocompatibility, biodegradability, and skin-friendliness, making it a good environmentally friendly material. However, its strength and abrasion resistance are generally low when used in nonwoven fabrics. While maleic anhydride-terminated carboxyl-terminated PLA can improve its mechanical strength through melt grafting, its abrasion resistance still fails to meet the requirements for nonwoven fabric applications. This invention involves reacting maleic anhydride-terminated carboxyl-terminated PLA with chitosan, polyether polyamine, and trimesoyl chloride. The amino groups of chitosan and polyether polyamine, as well as the hydroxyl groups in chitosan, undergo N-acylation and O-acylation reactions with the anhydride in the grafted maleic anhydride, thereby introducing chitosan, with its excellent tear resistance and abrasion resistance, into the PLA branch chains. Simultaneously, because polyether polyamine is multifunctional, it can form a cross-linked network structure within the branch chains. Furthermore, trimesoyl chloride, a multifunctional small-molecule rigid substance, can react with the hydroxyl groups on chitosan, forming localized rigid cross-linking points throughout the system, further enhancing the system's strength. In other words, after the above modification, while preserving the main chain structure of polylactic acid, a cross-linked network structure is formed in its branch structure, and the chitosan in the branch structure is also environmentally friendly. Thus, while basically maintaining the environmental protection characteristics of polylactic acid, its mechanical strength and wear resistance are improved.

[0026] Bicomponent fibers with a side-by-side structure are composite fibers in which two components are arranged side-by-side in the same fiber, with a continuous and clear interface between the two components along the fiber axis. The modified polylactic acid (PLA) has increased molecular rigidity and strength, resulting in a lower heat shrinkage rate in the fibers made from it. High-shrinkage polyester (HSPET), on the other hand, has a relatively high shrinkage rate, leading to a significant difference in their heat shrinkage properties. Therefore, when modified PLA and high-shrinkage polyester are spun in a side-by-side composite, varying degrees of shrinkage during the spinning process cause helical crimping, resulting in a fluffy bicomponent fiber that further imparts softness and skin-friendly properties.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] This invention first involves melting maleic anhydride to graft carboxyl-terminated polylactic acid (PLA), then reacting it with chitosan, polyether polyamine, and trimesoyl chloride to obtain modified PLA. Next, the modified PLA is composite-spun with high-shrinkage polyester to obtain a bicomponent fiber with a parallel structure. Finally, a wear-resistant and environmentally friendly spunlace nonwoven fabric is produced through web laying and hydroentangling processes. In this invention, after modification, the PLA's main chain structure remains essentially unchanged, while a cross-linked network structure is formed in its branched structure. This essentially maintains the good biocompatibility, degradability, and skin-friendliness of PLA while improving its mechanical strength and wear resistance. Furthermore, the composite spinning of the modified PLA with high-shrinkage polyester to obtain a bicomponent fiber with a parallel structure results in a spiral curl due to the significant difference in thermal shrinkage properties between the two components during the spinning process. This makes the resulting bicomponent fiber fluffy, further endowing it with softness and skin-friendliness. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. The following embodiments are provided to better understand this invention, but do not limit the invention. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods.

[0030] Unless otherwise specified, "parts" in the embodiments of the present invention refers to parts by mass, and "%" refers to percentage by mass unless otherwise specified.

[0031] Carboxyl-terminated polylactic acid was purchased from Ningbo Huanqiu Biotechnology Co., Ltd., with an intrinsic viscosity of 1.40±0.02 dl / g and a melting point of 170±2℃.

[0032] Chitosan was purchased from Jinan Haidebei Marine Bioengineering Co., Ltd., with an intrinsic viscosity of 2.2±0.02 dl / g and a degree of deacetylation of 85%.

[0033] The polyether triamine T-403 was purchased from Huntsman and has a molecular weight of approximately 400.

[0034] The high-shrinkage polyester chips were purchased from Zhejiang Hengyi High-Tech Materials Co., Ltd., with an intrinsic viscosity of 0.68±0.01 dl / g and a melting point of 206±2℃.

[0035] Preparation of modified polylactic acid

[0036] Preparation Example 1

[0037] (L1) 100 parts of carboxyl-terminated polylactic acid (PLA) chips and 5 parts of maleic anhydride were dried in a drying oven at 70°C for 8 hours. The dried PLA chips, maleic anhydride and 0.1 parts of ditert-butyl peroxide were mixed evenly and then melt-grafted in a twin-screw extruder at 190°C for 1 hour with a screw speed of 80 r / min. The reaction extrudate was cooled in a cooling water bath to obtain grafted PLA chips.

[0038] (L2) Under a nitrogen atmosphere, all the grafted polylactic acid obtained in step (L1), 6 parts chitosan, 2 parts polyether triamine T-403, and 0.03 parts anhydrous FeCl3 were dissolved in a mixture of DMF and oxalic acid (oxalic acid accounted for 2% of the volume in the mixture). The mixture was reacted at 8°C for 2 hours, and then heated to 70°C for another 3 hours. After cooling to room temperature, 0.25 parts trimesoyl chloride and 0.4 parts pyridine were added, and the mixture was reacted at 15°C for 1 hour. After the reaction was completed, the mixture was rotary evaporated, dried to constant weight, and granulated to obtain modified polylactic acid.

[0039] Preparation Example 2

[0040] The rest is the same as in Preparation Example 1, except that the amount of raw materials used in step (L2) is: 6.5 parts chitosan, 2 parts polyether triamine T-403, 0.04 parts anhydrous FeCl3, 0.3 parts trimesoyl chloride, and 0.5 parts pyridine.

[0041] Preparation Example 3

[0042] The rest is the same as in Preparation Example 1, except that the amount of raw materials used in step (L2) is: 7 parts chitosan, 2.5 parts polyether triamine T-403, 0.04 parts anhydrous FeCl3, 0.35 parts pyromellitic trimethylol chloride, and 0.6 parts pyridine.

[0043] Preparation Example 4

[0044] The rest is the same as in Preparation Example 1, except that the amount of raw materials used in step (L2) is: 7.5 parts chitosan, 3 parts polyether triamine T-403, 0.05 parts anhydrous FeCl3, 0.4 parts pyromellitic trimethylol chloride, and 0.7 parts pyridine.

[0045] Preparation Example 5

[0046] The rest is the same as in Preparation Example 1, except that the amount of raw materials used in step (L1) is: 100 parts of carboxyl-terminated polylactic acid chips, 8 parts of maleic anhydride, and 0.2 parts of ditert-butyl peroxide; the amount of raw materials used in step (L1) is: 9.6 parts of chitosan, 3.2 parts of polyether triamine T-403, 0.05 parts of anhydrous FeCl3, 0.4 parts of trimesoyl chloride, and 0.7 parts of pyridine.

[0047] Comparative Preparation Example 1

[0048] The rest is the same as in Preparation Example 1, except that in step (L2), chitosan is replaced with an equal mass of 1-amino-1-deoxy-D-sorbitol.

[0049] Comparative Preparation Example 2

[0050] The rest is the same as in Preparation Example 1, except that polyether triamine T-403 is not added in step (L2).

[0051] Comparative preparation example 3

[0052] The rest is the same as in Preparation Example 1, except that step (L2) is omitted.

[0053] Example 1

[0054] 1) Modified polylactic acid and high-shrinkage polyester chips were dried separately in a rotary drum drying oven at 75°C for 12 hours; 40 parts of the dried modified polylactic acid prepared in Preparation Example 1 were added to a twin-screw extruder for heating and melting (feed section temperature 180°C, compression section temperature 200°C, metering section temperature 215°C), and then passed through a melt filter, melt conveying pipeline, and metering pump into the spinning die. After passing through the spinning die (temperature 235°C), the melt was evenly distributed to the first spinning assembly; 60 parts of the dried high-shrinkage polyester chips were added to the twin-screw extruder for heating and melting. The ester is added to another twin-screw extruder for heating and melting (feed section temperature 200℃, compression section temperature 215℃, metering section temperature 225℃). It then passes through a melt filter, melt delivery pipeline, and metering pump into the spinning die (temperature 235℃). After passing through the spinning die, it is evenly distributed to the second spinning assembly. At the outlet, it undergoes composite spinning, followed by cooling, stretching, winding, and cutting to produce a high-shrinkage polyester / modified polylactic acid bicomponent fiber with a fineness of 2.2 dtex and a length of 35 mm.

[0055] 2) The bicomponent fibers with the parallel structure obtained above are opened, fed into a carding machine, and cross-laid to form a web with a basis weight of 25 g / m². 2 The fiber web layer is then fed into a high-pressure hydroentanglement zone for reinforcement with 8 MPa hydroentanglement, with 5 hydroentanglement passes. After drying at 120°C and rolling, a wear-resistant and environmentally friendly hydroentangled nonwoven fabric is obtained.

[0056] Examples 2-5

[0057] The rest is the same as in Example 1, except that in step 1), the modified polylactic acid was prepared in Examples 2-5.

[0058] Example 6: Modified polylactic acid accounts for 50% of the bicomponent fiber.

[0059] The rest is the same as in Example 1, except that in step 1), the amount of modified polylactic acid obtained from Preparation Example 1 after drying is 50 parts, and the amount of high-shrinkage polyester after drying is 50 parts.

[0060] Comparative Examples 1-3

[0061] The rest is the same as in Example 1, except that in step 1), the modified polylactic acid was prepared in Comparative Preparation Examples 1-3.

[0062] Testing and Analysis

[0063] The spunlace nonwoven fabrics prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0064] Abrasion resistance: The test shall be conducted in accordance with the provisions of GB / T 21196.2-2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage". The test conditions are: friction load of 3 kPa, standard wool felt; record the total number of frictions when the specimen breaks to determine its abrasion resistance. The higher the total number of frictions when the specimen breaks, the better the abrasion resistance.

[0065] Softness: The transverse softness and longitudinal softness are measured according to the test method of standard GB / T 8942-2016. The larger the value, the worse the softness.

[0066] Degradability test: The test shall be conducted in accordance with the provisions of GB / T 19277.1-2011 "Determination of final aerobic biodegradability of materials under controlled composting conditions by means of determination of carbon dioxide released - Part 1: General method".

[0067] The test results are shown in Table 1.

[0068] Table 1 Performance Tests

[0069]

[0070]

[0071] As can be seen from Table 1, the spunlace nonwoven fabric prepared in the embodiments of the present invention has excellent abrasion resistance and good biodegradability, and is also skin-friendly and soft, thus balancing abrasion resistance and environmental friendliness. The nonwoven fabric prepared in Comparative Example 1 has insufficient abrasion resistance and biodegradability / environmental friendliness. Although the nonwoven fabric prepared in Comparative Example 2 has good biodegradability and skin-friendliness, its abrasion resistance is also insufficient. Although the nonwoven fabric prepared in Comparative Example 3 has excellent biodegradability and skin-friendliness, its abrasion resistance is poor.

[0072] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A wear-resistant and environmentally friendly spunlace nonwoven fabric, characterized in that, It is composed of a bicomponent fiber with a high-shrinkage polyester / modified polylactic acid parallel structure. The modified polylactic acid is obtained by melt grafting maleic anhydride onto carboxyl-terminated polylactic acid, followed by reaction with chitosan, polyether polyamine, and trimesoyl chloride. The amount of maleic anhydride used is 5-8 wt% of the carboxyl-terminated polylactic acid. The mass ratio of maleic anhydride, chitosan, polyether polyamine, and trimesoyl chloride is 1:(1.2-1.5):(0.4-0.6):(0.05-0.08). The modified polylactic acid is prepared by a method including the following steps: (L1) Carboxyl-terminated polylactic acid, maleic anhydride and initiator are mixed and melt-grafted to obtain grafted polylactic acid; (L2) Grafted polylactic acid, chitosan, polyether polyamine and catalyst are dissolved in a solvent and reacted at 5~10℃ for 2~4h under an inert atmosphere, and then the temperature is raised to 60~80℃ and the reaction is continued for 2~4h; then pyromellitic acid chloride and acid binding agent are added and reacted at 10~25℃ for 0.5~1h. After the reaction is completed, rotary evaporation and drying are performed to obtain modified polylactic acid.

2. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 1, characterized in that, The mass ratio of maleic anhydride, chitosan, polyether polyamine, and trimesoyl chloride is 1:(1.3~1.4):(0.4~0.5):(0.06~0.07).

3. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 1, characterized in that, In step (L1), the initiator is selected from at least one of dicumyl peroxide and di-tert-butyl peroxide, and the amount of initiator used is 0.1~0.2wt% of the carboxyl-terminated polylactic acid; the melt grafting conditions are: carried out in a twin-screw extruder, reaction temperature 180~200℃, time 0.5~1.5h; and / or In step (L2), the catalyst is at least one of FeCl3 and AlCl3, and the amount of catalyst used is 0.5~0.8 wt% of chitosan; the solvent is a mixture of a polar aprotic organic solvent and an organic acid, wherein the volume percentage of the organic acid is 1~3%, the polar aprotic organic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone, and the organic acid is at least one of acetic acid, oxalic acid, and citric acid; the inert atmosphere is nitrogen and / or argon; the acid-binding agent is selected from at least one of triethylamine and pyridine, and the mass of the acid-binding agent is 1.5~2.0 times that of trimesoyl chloride.

4. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 1, characterized in that, In the bicomponent fiber with the parallel structure, the mass ratio of modified polylactic acid is 40-50%, and the remainder is high-shrinkage polyester.

5. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 1, characterized in that, The parallel-structured bicomponent fiber has a fineness of 1.5~3.0 dtex and a length of 30~50 mm. The parallel-structured bicomponent fiber is prepared by a method including the following steps: modified polylactic acid is added to an extruder and heated to melt, then enters the spinning die through a melt filter, melt conveying pipeline, and metering pump, and is evenly distributed to the first spinning assembly through the spinning die; high-shrinkage polyester is added to another extruder and heated to melt, then enters the spinning die through a melt filter, melt conveying pipeline, and metering pump, and is evenly distributed to the second spinning assembly through the spinning die; composite spinning is performed at the outlet, followed by cooling, stretching, winding, and cutting to produce the parallel-structured bicomponent fiber.

6. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 5, characterized in that, The high-shrinkage polyester and modified polylactic acid are dried at 65-80°C for 8-12 hours before being fed into the extruder, and the composite spinning temperature is 230-250°C.

7. The wear-resistant and environmentally friendly spunlace nonwoven fabric according to claim 1, characterized in that, The high-shrinkage polyester has an intrinsic viscosity of 0.65~0.72 dl / g and a melting point of 200~220℃; the carboxyl-terminated polylactic acid has an intrinsic viscosity of 1.30~1.50 dl / g and a melting point of 160~190℃; the chitosan has an intrinsic viscosity of 2.0~2.5 dl / g and a degree of deacetylation of 80~90%; the polyether polyamine is at least one of polyether diamine and polyether triamine, and the number average molecular weight of the polyether polyamine is 400~1000.

8. The method for preparing the wear-resistant and environmentally friendly spunlace nonwoven fabric according to any one of claims 1-7, characterized in that, Includes the following steps: The high-shrinkage polyester / modified polylactic acid bicomponent fibers are opened and carded into a web to form a fiber web layer; then, after hydroentangling reinforcement, drying, and rolling, a wear-resistant and environmentally friendly hydroentangled nonwoven fabric is obtained.

9. The preparation method according to claim 8, characterized in that, The combing process involves parallel or cross-laid web formation; the hydroentangling reinforcement process involves a hydroentangling pressure of 4-10 MPa and 3-6 hydroentangling passes.

Citation Information

Patent Citations

  • Polypropylene (PP) spun-bonded nonwoven fabric fully-degradable composite material and preparation method thereof

    CN102336929B

  • PP (Polypropylene) spun-bonded non-woven fabric degradable composite material and preparation process thereof

    CN102336961B

  • Production method of double-component spinneret outside composite parallel self-crimping elastic short fiber

    CN106149071A

  • Two-component composite electret fiber and preparation method and application thereof

    CN115418744A